2020
DOI: 10.1016/s2213-8587(20)30104-2
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of intradermal injection with tolerogenic dendritic cells pulsed with proinsulin peptide—for type 1 diabetes

Abstract: overdiagnosis after 2012 remains yet largely unknown, the extent of overdiagnosis indicates an urgent need to closely monitor its evolution worldwide and the impact of recent guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 6 publications
0
61
0
Order By: Relevance
“…TolDCs display a differential transcriptome compared with inflammatory DCs that is unaffected by health status or production location Stability of a cellular product, including reproducible production between different international centers and between healthy subjects and T1D patients, is important for its implementation in the clinic. Therefore, the authors produced tolDCs from healthy subjects and T1D patients that passed validated quality control criteria (low CD86 expression, high CD52 expression [27]) in two international production centers. Subsequently, for more in-depth analysis, a transcriptome study was conducted comparing gene expression by RNA-seq between DCs produced at LUMC and COH.…”
Section: Toldcs Retain Semi-mature Functional Aspects and Metabolism mentioning
confidence: 99%
“…TolDCs display a differential transcriptome compared with inflammatory DCs that is unaffected by health status or production location Stability of a cellular product, including reproducible production between different international centers and between healthy subjects and T1D patients, is important for its implementation in the clinic. Therefore, the authors produced tolDCs from healthy subjects and T1D patients that passed validated quality control criteria (low CD86 expression, high CD52 expression [27]) in two international production centers. Subsequently, for more in-depth analysis, a transcriptome study was conducted comparing gene expression by RNA-seq between DCs produced at LUMC and COH.…”
Section: Toldcs Retain Semi-mature Functional Aspects and Metabolism mentioning
confidence: 99%
“…Monocyte derived tolerogenic DCs (tolDcs) from patients under sub-optimal glycemic control display reduced tolerogenic capabilities compared to those from patients under optimal control (45)(46)(47)(48). However, this glycemia dependent difference may not necessarily be a general difference between health and disease, and could be a consequence, rather than causally related to T1D immunopathogenesis.…”
Section: Myeloid Cells In Circulation In Health and Diseasementioning
confidence: 99%
“…However, this glycemia dependent difference may not necessarily be a general difference between health and disease, and could be a consequence, rather than causally related to T1D immunopathogenesis. We recently showed that tolDCs generated from T1D patients' blood induce immune tolerance indifferently from those from healthy individuals, proving that they still possess their immune-regulatory capacity (47).…”
Section: Myeloid Cells In Circulation In Health and Diseasementioning
confidence: 99%
“…An alternative approach to infusing ex vivo-expanded Tregs is to use tolerogenic APCs to expand Tregs in vivo by exploiting infectious tolerance, an approach which bypasses the risk of compromising Treg stability during ex vivo expansion [80]. Several clinical studies have now assessed tolAPC therapy in treating type 1 diabetes [81,82], rheumatoid arthritis [83,84], Crohn's disease [85], multiple sclerosis and neuromyelitis optica spectrum disorders [86] and preventing kidney transplant rejection [74]. These studies used multiple methods to derive autologous, "immature" tolDCs (or regulatory macrophages [74]) from patient monocytes, some involving disease-relevant antigen pulsing prior to injection [82,84,86].…”
Section: In Vivo Expansion Of Treg Cellsmentioning
confidence: 99%
“…Several clinical studies have now assessed tolAPC therapy in treating type 1 diabetes [81,82], rheumatoid arthritis [83,84], Crohn's disease [85], multiple sclerosis and neuromyelitis optica spectrum disorders [86] and preventing kidney transplant rejection [74]. These studies used multiple methods to derive autologous, "immature" tolDCs (or regulatory macrophages [74]) from patient monocytes, some involving disease-relevant antigen pulsing prior to injection [82,84,86]. Studies to date showed these therapies were well tolerated with small increases in peripheral Treg numbers [81,[84][85][86].…”
Section: In Vivo Expansion Of Treg Cellsmentioning
confidence: 99%